The Path to Innovation: The Antecedent Perspective of Intellectual Capital and Organizational Character - Li, Jingyi; Yu, Dengke (Frontiers in Psychology, 2018)
Purpose: The high-speed growth of China's large-scale new economy indicates that innovation has become the most important economic growth pole. The study aims to explore the structure of the path to innovation, in which we focus on the mediating effect of organizational character. Design/methodology/approach: Considering the indigenous context of China's new economy, the study divides innovation into two types: technological innovation and business model innovation. Then, we build a path model to achieve the innovation by taking intellectual capital and organizational character as antecedents. Finally, a structural equation model is built to measure the path on the basis of sample data collected via a questionnaire survey. Findings: The results indicate that intellectual capital has a significant positive direct effect on technological innovation, but its direct effect on business model innovation is not significant. Organizational character not only mediates the relationship between the intellectual capital and technological innovation, but also plays a mediating role in the effect path from the intellectual capital to business model innovation. In addition, technological innovation has a positive impact on the business model innovation, and mediates the relationship between the intellectual capital and business model innovation. Originality/value: The study takes intellectual capital and organizational character as the common antecedents of innovation and breaks down the content of innovation research into technological innovation and business model innovation. Thus, it establishes a new theoretical analysis framework for dual innovation research and enriches the related theories. The framework would have stronger explanatory power for revealing the innovation strategy and behavior carried out by a large number of corporate organizations in China and the boom of new economy. Furthermore, it would lead enterprises to organize innovation activities more effectively and improve their innovation performances.